2001
DOI: 10.1051/0004-6361:20011280
|View full text |Cite
|
Sign up to set email alerts
|

Optical spectra of five UX Orionis-type stars

Abstract: Abstract. We present in this paper several high resolution (R = 27 000) spectra of five UXORs (UX Ori, CQ Tau, BF Ori, RR Tau, WW Vul), which cover the entire visual range, from 3900 to about 8700Å. There are between 4 and 7 spectra per star, obtained over a time interval of two years. Simultaneous or quasi-simultaneous photometric observations were also obtained at the Crimean Astrophysical Observatory. The complete, reduced and normalized spectra are available in electronic form. We show for each star a sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
39
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 19 publications
6
39
0
Order By: Relevance
“…They are also observed in many other lines (e.g. He , Fe  and Fe ), as already pointed out by Grinin et al (2001), but a corresponding discussion is deferred to a future work.…”
Section: R Multicomponent Gaussian Fittingsupporting
confidence: 61%
“…They are also observed in many other lines (e.g. He , Fe  and Fe ), as already pointed out by Grinin et al (2001), but a corresponding discussion is deferred to a future work.…”
Section: R Multicomponent Gaussian Fittingsupporting
confidence: 61%
“…All kinds of shapes from the classification by Reipurth et al are observed: P Cygni, single-and doublepeaked (see, e.g., Böhm & Catala 1995;Grinin et al 2001;Mora et al 2001;Feigelson et al 2003;Beskrovnaya & Pogodin 2004;Movsessian et al 2008;Grady et al 2011;Montesinos 2009;Mendigutía 2012). Such a vast sample of profile shapes suggests that this line originates in a very complex environment possibly including the accretion disk, disk wind, jet, and magnetosphere.…”
Section: Hybrid Model: Disk Wind X-wind and Magnetospherementioning
confidence: 93%
“…Observations of Herbig Ae/Be stars (e.g., Finkenzeller & Mundt 1984;Reipurth et al 1996;Drew et al 1997;Grinin et al 2001) reveal very wide Balmer lines in the spectra of some stars. For optically thick lines such as Hα, Stark broadening can cause the observed line widths.…”
Section: Stark Effectmentioning
confidence: 99%
“…Then the distance of the star could be varied within the margins of its uncertainty, implying a corresponding variation of A cs v , which should be limited to positive values. We then varied the inclination angle i of the disc and the extinction law R cs in order to improve the agreement in the Finkenzeller (1985) 11: Walter et al (1987) 20: Martin (1993 29: Meeus et al (1998) 38: Hartmann et al (1989) 3: Hillenbrand et al (1992) 12: Grady et al (1996 21: Bessel & Eggen (1972) 30: Sylvester et al (1996 39: Elias (1978b) 4: Slettebak (1982 13: Herbig & Bell (1988) Shevchenko et al (1997) 15: Herbertz et al (1991 24: Artyukhina (1960) 33: Beskrovnaya et al (1999) 42: Appendix C.41 7: Joncour et al (1994) 16: Friedemann et al (1993) 25: Fernández et al (1995) 34: Glagolevskii et al (1998 43: Appendix C.43 8: Herbig (1966) 17: Finkenzeller & Mundt (1984) 26: Reipurth et al (1996) 35: Wallenquist (1937 44: Mora et al (2001) 9: Andersen et al (1989 18: Kolotilov & Zajtseva (1974) 27: Pérez et al (2004) 36: v.d.Ancker et al (2000 45: Grinin et al (2001) LW (λ > 2000 Å) spectral range. After that M v , δ bl , and R cs were slightly adjusted until the match was optimal.…”
Section: The Iue Spectral Analysismentioning
confidence: 97%